Synthesis of visible and near infrared light sensitive amorphous titania for photocatalytic hydrogen evolution. Issue 7 (26th November 2015) - Jiang, Jinghui; Tang, Xingwei; Zhou, Shujun; Ding, Jian; Zhou, Han; Zhang, Fan; Zhang, Di; Fan, Tongxiang
Abstract : An anaerobic hydrolysis of titanium metal was designed to synthesize visible and near infrared light sensitive amorphous titania. Abstract : A simple and environmentally safe method of anaerobic hydrolysis was designed to synthesize amorphous TiO2− x containing Ti 3+ from the dissolution of Ti 0 by water in an anaerobic environment. The disordered arrangement of atoms in amorphous TiO2− x enables it to expand its light absorbing boundary from the ultraviolet to near infrared light region by narrowing its mobility gap to 1.5 eV. As a result, an effective visible and near infrared light photocatalytic hydrogen evolution from water splitting can be achieved by the as-synthesized amorphous TiO2− x with the aid of Ti 3+ to inhibit charge recombination. An ideal quantum yield of approximately 4.57% was achieved at a wavelength of 488 nm. This strategy represents a new approach to alter the activity of TiO2, and it is meaningful for achieving green production of artificial clean energy.